Sports: A Smart Life and an Integrated Strategy for Digital Transformation and its Impact on Sustainable Institutional Development in the Sports System - Ghazi, Dr. Muhammad Asim (Sulaimani Journal for Humanities, 2026)
This study, "Sports as a Smart Life and an Integrated Strategy for Digital Transformation and its Impact on Sustainable Institutional Development in the Sports System," highlights the importance of digital transformation in enhancing the effectiveness of sports organizations. These organizations face increasing challenges due to technological advancements, necessitating the development of integrated strategies that incorporate modern technologies into their management. The findings indicate that 65% of sports organizations lack clear digital transformation strategies, and 70% suffer from weak digital infrastructure. The study aims to develop an integrated digital transformation strategy by analyzing the current situation and identifying the necessary requirements, thereby enhancing institutional sustainability. The study employs a descriptive-analytical methodology and collects data from a representative sample of various segments within the sports community. It also includes a questionnaire assessing the impact of digital transformation on sports performance and institutional sustainability. Preliminary results indicate a positive correlation between the application of smart technologies and improved operational efficiency. The significance of this study lies in its provision of a comprehensive strategic model that can contribute to improving institutional performance, increasing the effectiveness of internal processes, and fostering innovation. Therefore, this study represents an important scientific reference for officials and researchers in the field of sports management, opening new horizons for sustainable development in the sports sector
Keywords: Sports A Smart Life; an Integrated Strategy for Digital Transformation; and Sustainable Institutional Development in the Sports System